Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Konsumen JNE Cabang Lubuk Pakam - Nur Indah Sari, Tri Anggi (Jurnal Manajemen Bisnis dan Keuangan, 2021)
This study aimed to analyze the variables of price and service quality in influencing consumer satisfaction at PT. JNE Express Lubuk Pakam branch. The data is taken from the primary source (primary) with the probability sampling technique and secondary sources. The number of samples in this study was 160 respondents. The data collected from the respondents were then analyzed by multiple linear regression. The data and research models have also met the classical assumption test so that the conclusions drawn can be valid and unbiased. This study indicates that the variables of price and service quality are significant in influencing consumer satisfaction of PT. JNE Express Lubuk Pakam branch.